HUBUNGAN ANTARA TINGKAT PENGETAHUAN IBU TENTANG PERMAINAN EDUKATIF DENGAN STIMULASI PERKEMBANGAN ANAK PADA IBU-IBU DESA PEPE KELURAHAN LANGENHARJO - Endang Dwi Ningsih; Ratna Indriati; Jumiati Jumiati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. The Golden Years is the best period for a child’s growing fastest,by giving stimulus correctly on the top of the growing period, is a possibility forthe child geting an optimum prestation. Knowledge or the cognition aspect is animportant domain to the overt behavior.The purpose of the study was to determine the relation between a mothersknowing of the edu-games ( educational games) with a child growing stimulus inPepe Village, Langenharjo, Grogol, SukoharjoMethod was a correlation method with cross sectional approach. The subjectwas all 32 mothers who have children aged between 0-5 years old. Samplingtechnique used was total sampling. From the data’s analized by X2 count > X2table (6,12 > 5,59) with sigificant level 5%.The study concluded there was any significant relation between a mothersknowing of the educational game with the child growing stimulus in the PepeVillage, Langenharjo, Grogol, Sukoharjo.Keywords : Level of Knowledge and Stimulation